The Site-specific Protonation Constants of Spectinomycin, Characterized by 1H and 15N NMR Methods - Somlyay, Mate; Orgovan, Gabor; Noszal, Bela (Current Pharmaceutical Analysis, 2015)
Spectinomycin, a tricyclic aminoglycoside antibiotic with peculiar chemical structure and pharmacological profile was characterized in terms of microscopic protonation constants. 1H-15N HMBC-pH titrations were carried out to allocate the order of basicities of the two similar methylamino functions of spectinomycin, and 1H NMR-pH titrations were performed on spectinomycin and actinamine, its symmetrical model compound to determine the basicity of the amino sites. It was found that the methylamino moiety in position 3 is of some 60% higher basicity than its counterpart in position 1, and protonation at one site decreases the basicity of the other site by 1.17 logk units. Both secondary amino sites as such are of relatively low basicity, due to the adjacent, electron-withdrawing 7 oxygens. At the pH of blood nearly equal amounts of di- and monocationic species coexist, while less than 1% of neutral spectinomycin occurs at this pH. The pHdependent distribution of the microspecies is depicted.
Keywords: microspeciation